Theoretical aspects of selection of optimal design parameters of a new generation of AC transmission lines - Postolati V.M.; Suslov V.M. (Problems of the Regional Energetics)
The problems of compactness and of a choice of optimal parameters of alternating current transmission lines are considered. Analytical analysis of some constructive characteristics of three variants of lines of new generation (one-chain, two-chain and operated self-compensated), for the purpose of their optimization by criteria of the maximum compactness is performed.